Of Freedom and Free Trade. - Gerken, Lüder (Routledge, 2004)
This book, a well-argued treatise on the benefits of neo-classical free trade, develops the principles of a liberal foreign trade theory and provides a new conceptual basis for discussing the argument between free-trade and protectionism.